Comparative Analysis of The Influence of Sharia and Conventional Monetary Instruments on The Real Sector: An Empirical Study of Indonesia's IPI - Ahmad Suminto; Ahmad Agus Hidayat; Risma Nada Azkiya; Rumasukun, Muhammad Alfan; Purnama, Rizki Ari (MUSLIM HERITAGE, 2024)
Abstract Indonesia implements a dual monetary policy system, namely conventional and sharia systems that run side by side. The conventional system is a system of interest, while the Sharia system is a system of profit-sharing. The role of the monetary sector in Indonesia's economic growth is very important by minimizing transaction costs or information in financial markets. To ensure the smooth flow of economic activities and enhance the productivity of individuals in the production of goods and services in the real sector. The purpose of this study is to determine the influence of Islamic and conventional monetary instruments on the real sector. This study uses quantitative methods with an Autoregressive Distributed Lag (ARDL) estimation model with the Industrial Production Index (IPI) as the dependent variable. Bank Indonesia Sharia Certificates (SBIS), Sharia Interbank Money Market (PUAS) and financing as independent variables of Islamic monetary instruments, while Bank Indonesia Certificates (SBI), Interbank Money Market (PUAB) and credit as independent variables of conventional monetary instruments. The results of this study show that Islamic and conventional monetary instruments as a whole affect the Industrial Production Index (IPI) as a real sector with an influence of 77% on Islamic monetary instruments and 45% on conventional monetary instruments. In this study, the variables that affect IPI are SBIS, PUAS, financing and interbank while SBI and credit variables do not affect IPI. Abstrak Indonesia menerapkan sistem kebijakan moneter ganda yaitu sistem konvensional dan syariah yang berjalan berdampingan. Penerapan pada sistem konvensional dengan sistem bunga sedangkan pada sistem syariah menganut sistem bagi hasil. Peran sektor moneter pada pertumbuhan ekonomi Indonesia sangatlah penting dengan meminimalisir biaya transaksi ataupun informasi di pasar keuangan. Sehingga kegiatan ekonomi berjalan lancar dan dapat meningkatkan produktifitas masyarakat dalam menghasilkan barang dan jasa di sektor riil. Tujuan penelitian ini untuk mengetahui pengaruh dari instrumen moneter syariah dan konvensional terhadap sektor riil. Penelitian ini menggunakan metode kuantitatif dengan model estimasi Autoregressive Distributed Lag (ARDL) dengan Indeks Produksi Industri (IPI) sebagai variabel dependen. Sertifikat Bank Indonesia Syariah (SBIS), Pasar Uang Antar Bank Syariah (PUAS) dan pembiayaan sebagai variabel independen dari instrumen moneter syariah, sedangkan Sertifikat Bank Indonesia (SBI), Pasar Uang Antar Bank (PUAB) dan kredit sebagai variabel independen dari instrumen moneter konvensional. Hasil dari penelitian ini menunjukkan bahwa instrumen moneter syariah dan konvensional secara keseluruhan berpengaruh terhadap Indeks Produksi Industri (IPI) sebagai sektor riil dengan pengaruh sebesar 77% pada instrumen moneter syariah dan 45% pada instrumen moneter konvensional. Dalam penelitian ini, variabel yang berpengaruh terhadap IPI adalah SBIS, PUAS, pembiayaan dan PUAB sedangkan variabel SBI dan kredit tidak berpengaruh terhadap IPI. Keywords: Sharia Monetary; Conventional Monetary; Real Sector and Industrial Production Inde